2018
DOI: 10.1007/s10902-018-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction in Russian Primary Schoolchildren: Links with Personality and Family Environment

Abstract: The present study aimed to investigate life satisfaction and its relations to family environment and child personality in a large community sample of Russian primary schoolchildren aged 7-10 years (N = 705, 51% female). Children completed Huebner's Student's Life Satisfaction scale; parents reported about family background and completed the Alabama Parenting Questionnaire-Brief Form, the Self Reporting Questionnaire measuring parental stress and the Inventory of Child Individual Differences-Short version measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
21
0
1
Order By: Relevance
“…The statements are overall evaluations of the young person's life, for example: "My life is going well". The Russian version has been validated, supporting good reliability of the scale (Leto, Petrenko, & Slobodskaya, 2018). In the present study, alpha was .74.…”
Section: Methodssupporting
confidence: 75%
“…The statements are overall evaluations of the young person's life, for example: "My life is going well". The Russian version has been validated, supporting good reliability of the scale (Leto, Petrenko, & Slobodskaya, 2018). In the present study, alpha was .74.…”
Section: Methodssupporting
confidence: 75%
“…[ 1 ] demonstrates that household composition and the length of time a family remain living in a city are not associated with satisfaction with life in that place. However, other studies [ 49 ] report that life satisfaction is significantly correlated, albeit weakly, with the family situation, essentially with the composition of the family (parents’ marital status, number of children, etc.). For example, the size of the family unit has a positive impact on individual happiness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AFCS should also be positively associated with a positive mindset and personality dimensions, such as selfcompassion [11], satisfaction with life [4][5][6][7], agreeableness and conscientiousness [1][2][3]. In contrast, it should be negatively correlated with neuroticism [1][2][3], depression, anxiety and stress [8][9][10][11][12][13]. On the other hand, the literature suggested that the AFCS would have a low or nonsignificant association with extraversion and openness to experience [1,2].…”
Section: Studymentioning
confidence: 99%
“…In contrast, it should be negatively correlated with neuroticism [1][2][3], depression, anxiety and stress [8][9][10][11][12][13]. On the other hand, the literature suggested that the AFCS would have a low or nonsignificant association with extraversion and openness to experience [1,2].…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation